Relative Hyperglycemia and Coronary Thrombosis in Diabetic STEMI: Current Evidence on the Prognostic Utility of Stress Hyperglycemia Ratio - Alaa El Sayed Salama, Mahmoud Hassan Abdelqader Shah, Ibrahim Mohamed Fathy Mohamed, Nada Hassan Metwally (Cuestiones de Fisioterapia, 2024)
Background: Diabetic patients presenting with ST-segment elevation myocardial infarction (STEMI) represent a particularly high-risk population characterized by more extensive coronary artery disease, enhanced platelet reactivity, impaired fibrinolysis, and an increased propensity for intracoronary thrombus formation. Large thrombus burden during primary percutaneous coronary intervention (PCI) is associated with distal embolization, no-reflow phenomenon, microvascular obstruction